FA01.06: ON THE RELATIONSHIP BETWEEN HISTOLOGY, ESOPHAGEAL-GASTRIC INTESTINAL METAPLASIA, GREATER CURVATURE LYMPHATIC METASTASES AND SURVIVAL IN SIEWERT II ADENOCARCINOMA. (14th September 2018) - Lugaresi, Marialuisa; Mattioli, Benedetta; Tassi, Valentina; Daddi, Niccolò; Ruffato, Alberto; Raulli, Gian; Malvi, Deborah; D'Errico, Antonietta; Mattioli, Sandro
Abstract: Background: In Siewert type II adenocarcinoma we investigated the relationship between adenocarcinoma subtypes and survival, histologic/biologic patterns related to the presence/absence of gastric greater curvature metastases. Methods: 154 patients who underwent primary transthoracic esophageal resection, total gastrectomy, thoracic-abdominal lymphadenectomy according to a research prospective protocol were considered. Cases were categorized in intestinal and diffuse subtypes, in Barrett's-like, cardiopyloric-like, and gastric-like adenocarcinoma according to the presence/absence of intestinal metaplasia in esophagus and stomach. Cancer specific survival and gastric greater curvature metastases were studied in those categories. Results: Pathological stage (7 th TNM ed) was IA-IIA in 11%; IIB in 15.6%; IIIA-IV in 73.4%. Cases were: 59% intestinal-type, 41% diffuse-type; Barrett's-type 1.3%, cardiopyloric-type 65%, gastric-type 33.7%. Greater gastric curvature lymph node metastases were detected in 22%, in stage IIIa-IV only, intestinal type 47%; diffuse type 53%. The number of metastatic lymph nodes at station 4 was higher in cardiopyloric-like than in gastric-like type ( P  < .0001).Five years cancer-specific survival of 154 cases was 40.5%, 59.4.% for intestinal type, 0% for diffuse type; 5-year cancer-specific survival in the absence/presence of greater gastric curvature metastases was respectively 48.7% and 14.9%, for intestinal type it was 67.4% and 27.9%. Histological subtype was an independent prognostic factor. Conclusion: The radical difference of 5 year survival between intestinal and diffuse types of Siewert type II adenocarcinoma after primary surgery, the relevant frequency and biologic patterns of station 4 nodal metastases do require further investigation in light of current indications for neoadjuvant therapy and total gastrectomy. Disclosure: All authors have declared no conflicts of interest.